2005
DOI: 10.4049/jimmunol.175.11.7447
|View full text |Cite
|
Sign up to set email alerts
|

Multiple TLRs Are Expressed in Human Cholangiocytes and Mediate Host Epithelial Defense Responses to Cryptosporidium parvum via Activation of NF-κB

Abstract: Infection of epithelial cells by Cryptosporidium parvum triggers a variety of host-cell innate and adaptive immune responses including release of cytokines/chemokines and up-regulation of antimicrobial peptides. The mechanisms that trigger these host-cell responses are unclear. Thus, we evaluated the role of TLRs in host-cell responses during C. parvum infection of cultured human biliary epithelia (i.e., cholangiocytes). We found that normal human cholangiocytes express all known TLRs. C. parvum infection of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
219
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(232 citation statements)
references
References 58 publications
10
219
0
1
Order By: Relevance
“…14,17,18,29,30 In the TLR family, TLR3 recognizes dsRNA and is located in the endosomal membranes with the ligand-binding domain facing the lumen of the endosomes and the signaling domain positioned on the cytoplasmic side. Therefore, TLR3 allows cells to detect dsRNA that is phagocytosed from the extracellular space, where it is released by infected cells that are undergoing lysis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,18,29,30 In the TLR family, TLR3 recognizes dsRNA and is located in the endosomal membranes with the ligand-binding domain facing the lumen of the endosomes and the signaling domain positioned on the cytoplasmic side. Therefore, TLR3 allows cells to detect dsRNA that is phagocytosed from the extracellular space, where it is released by infected cells that are undergoing lysis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We also previously demonstrated that TLR2 and TLR4 signals mediate cholangiocyte responses including production of human ␤-defensin 2 against C. parvum via TLR-associated activation of NF-B (11). Dominant negative TLR/MyD88 expressing cholangiocytes have diminished defenses against C. parvum infection in vitro (11). Thus, TLRs and the mechanisms involved in their regulation are key elements for cholangiocyte defense against C. parvum infection.…”
mentioning
confidence: 99%
“…We and others previously reported that human cholangiocytes express all 10 known TLRs and produce a variety of inflammatory cytokines/chemokines and antimicrobial peptides in response to microbial infection, suggesting a key but poorly understood role for cholangiocytes in epithelial defense (9 -14). We also previously demonstrated that TLR2 and TLR4 signals mediate cholangiocyte responses including production of human ␤-defensin 2 against C. parvum via TLR-associated activation of NF-B (11). Dominant negative TLR/MyD88 expressing cholangiocytes have diminished defenses against C. parvum infection in vitro (11).…”
mentioning
confidence: 99%
“…Non-coding RNAs are critical regulators of mucosal immunity to infection, while release of exosomes from epithelial cells may be a relatively unexplored, important part of mucosal anti-parasite defense. Conversely, it appears that Cryptosporidium has also developed strategies of immune evasion to escape host immunity, at least at the early stage of infection (Chen et al 2005).…”
Section: Resultsmentioning
confidence: 99%